2016
DOI: 10.1016/j.celrep.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

The AMPKα1 Pathway Positively Regulates the Developmental Transition from Proliferation to Quiescence in Trypanosoma brucei

Abstract: During infection in mammals, the protozoan parasite Trypanosoma brucei transforms from a proliferative bloodstream form to a quiescent form that is pre-adapted to host transition. AMP analogs are known to induce quiescence and also inhibit TbTOR4. To examine the role of AMP-activated kinase (AMPK) in regulation of this developmental transition, we characterized trypanosome TbAMPK complexes. Expression of a constitutively active AMPKα1 induces quiescence of the infective form and TbAMPKα1 phosphorylation occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 48 publications
2
67
0
Order By: Relevance
“…Bloodstream pleomorphic trypanosomes undergo differentiation from the proliferative to the quiescent stumpy form throughout mice infection. SNF2PH protein levels analysis in the pleomorphic AnTAT 90.13 strain decreased at 4-5 days postinfection (Appendix Fig S5C), whereas AMPKa1 was fully activated as previously described [42]. Taken altogether, these data suggest that SNF2PH is negatively regulated during transition to stumpy form and mechanistically linked to AMPKa1 activation by an undefined mechanism.…”
Section: Snf2ph Is Downregulated In Quiescent Stumpy Formssupporting
confidence: 81%
“…Bloodstream pleomorphic trypanosomes undergo differentiation from the proliferative to the quiescent stumpy form throughout mice infection. SNF2PH protein levels analysis in the pleomorphic AnTAT 90.13 strain decreased at 4-5 days postinfection (Appendix Fig S5C), whereas AMPKa1 was fully activated as previously described [42]. Taken altogether, these data suggest that SNF2PH is negatively regulated during transition to stumpy form and mechanistically linked to AMPKa1 activation by an undefined mechanism.…”
Section: Snf2ph Is Downregulated In Quiescent Stumpy Formssupporting
confidence: 81%
“…IPMK interacts with 5' adenosine monophosphate-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) and regulates glucose and amino acid signaling [31,32]. AMPK and target of rapamycin 4 (TOR4) complexes are also involved in T. brucei metabolism and development [2,3], but it is unknown if they associate with T. brucei IPMK. Moreover, the control of energy metabolism in T. brucei depends on IPMK catalytic activity and thus on IPs [6].…”
Section: Ip Regulation Of Energy Metabolism and Developmentmentioning
confidence: 99%
“…They also have elaborate mechanisms of gene regulation that control the expression of genes involved in host immune evasion during infection. The control of developmental changes and immune evasion mechanisms entails a complex network of signaling and regulatory processes that includes phosphatidylinositol (PI) phosphates (PIP, also called phosphoinositides) and inositol phosphates (IP) [2][3][4][5][6][7][8]. PIPs and IPs are ubiquitous in eukaryotes and consist of a subset of molecules containing mono or poly phosphorylated inositol ( Fig 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of stumpy cells that likely contribute to their survival in the fly midgut include their relative resistance to acidic and proteolytic stress [ 14 ]. For example, the differential response to mild acid conditions (pH 5.5) has been used as a selection to monitor the differentiation to stumpy cells in some studies [ 15 ], as slender cells are sensitive and stumpy cells are resistant. Moreover, protease treatment has been shown to act as a trigger for bloodstream forms to differentiate to procyclic cells [ 16 , 17 , 18 ].…”
Section: Characterisation Of Slender and Stumpy Cellsmentioning
confidence: 99%
“…More recently, Saldivia et al [ 15 ] have suggested that AMPKα1, and not the AMPKα2 that was identified in the Mony et al screen [ 102 ], is associated with the positive regulation of stumpy form development. In vitro phosphorylation analysis using an α-phospho-Thr172 antibody showed that AMPKα1 phosphorylation was significantly upregulated upon treatment with 8-pCPTAMP, whereas AMPKα2 phosphorylation levels were unaffected.…”
Section: Molecular Components Of the Slender To Stumpy Regulatory mentioning
confidence: 99%